The Role Tourism Technical Implementation Unit In Tete Tonra Beach Tourism Development Planning In Bone District - MR, Syaripa Aeni (Universitas Negeri Makassar, 2022)
The Role of the Tourism Technical Implementation Unit in the Tete Tonra Beach Tourism Development Planning in Bone district. This study aims to determine the role of the technical implementing unit of Tourism in planning the development of Tete Tonra Beach tourism in Bone district by using a qualitative design approach. This type of research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. The key informants of this research were the head of the tourism office of Bone Regency along with the head of the Technical Implementation Unit (UPT) and the manager of Tete Tonra Beach Tourism using an interactive model data analysis technique consisting of three activity flows that occurred simultaneously, namely: data condensation, data display, and conclusion drawing/verifications. The results showed that UPT Wisata had not yet shown an optimal role in the development planning of Tete Tonra Beach in Bone district. This can be seen from the results of development that have been carried out which show that the average has not been maximized, the lack of new breakthroughs, the lack of realization of the solutions that have been made, and the lack of routine evaluations carried out by the Tourism Office through the UPT.